The contribution of mining companies to social development through Corporate Social Responsibility - Jobo, Qhamani Naledi (My University, 2019)
ABSTRACT Mining continues to be a significant contributor to South Africa’s gross domestic product (GDP). The contribution of the mining sector to the country’s development is not only limited to the economy but extends to the socio-economic development of the communities within which mining operations occur. Government has through policy development, and the mining industry through policy implementation and voluntary acts, made inroads in addressing the social development challenges faced by mining communities. Despite these interventions however, mining communities are still largely characterised by major social challenges, and mining companies are often blamed for not doing enough to address this. This research was conducted in a bid to ascertain the contribution of mining companies to social development through Corporate Social Responsibility (CSR). The study adopted a qualitative case study design, focusing on The Mining Company’s Pinetown gold mine operations based in Westonaria, Gauteng. The participants for the study consisted of residents of the mining communities and leaders of various civic organisations in the communities, and key informants who are employees of The Mining Company in various capacities. A sample of eight participants and three key informants was drawn using the snowball sampling method. Data was collected through face to face interviews using semi-structured interview schedules. The findings revealed that there are various factors which influence the impact of The Mining Company’s CSR initiatives on social development in the surrounding communities. Chief among these is a misalignment between the company’s CSR initiatives and the social development priorities of the mining communities. This is underpinned by poor community engagement at the planning and design phase of CSR. Another is a lack of sustainability of the projects implemented, and this is largely influenced by ineffective monitoring and evaluation processes in the implementation phase. The report recommends a new approach to community engagement, particularly given that the company has been focusing on this and yet it still remains a challenge. Furthermore, the importance of and need for monitoring and evaluation of CSR projects cannot be overstated.
Keywords: Social responsibility of business. Mineral industries -- Social aspects. Mineral industries -- Environmental aspects.